Psychological Contract Breach and Turnover Intentions Among Lecturers: The Moderating Role of Organizational Climate - Kanu, Gabriel C.; Ugwu, Lawrence E.; Ogba, Francisca N.; Ujoatuonu, Ikechukwu V.; Ezeh, Michael A.; Eze, Adaobi; Okoro, Chinwendu; Agudiegwu, Moses; Ugwu, Leonard I. (Frontiers in Education, 2022)
Lecturing in private universities in Nigeria is among the challenging jobs for beginners. Regrettably, there is a high rate of turnover once an opportunity for exit presents itself. Researchers have proposed a relationship between psychological contract breach and turnover intentions. This study attempted to evaluate the effect of organizational climate in the link between psychological contract breach and turnover intentions using a sample of 584 private university lecturers in a two-wave investigation. The result suggested that lecturers who received support from management were less likely to leave their jobs while experiencing peace in the school played a significant factor in reducing turnover intention. The study's implications were raised, and further suggestions were made to improve our organizations, particularly universities.